Proposal for a method of measurement and control of surface quality in the course of abrasive waterjet cutting of material - Kmec, Ján; Harničárová, Marta; Cristina, Borzan; Borzan, Marian; Valíček, Jan; Kříž, Jiří; Kušnerová, Milena (EDP Sciences, 2019)
The paper deals with the automation of the hydroabrasive production process, which leads to higher productivity and production optimization. In the submitted work, the basis of control design is a topography function of surface roughness of abrasive waterjet cut walls, and its functional relations to the controlled speed and to the measured mean values of sound pressure level, including a design of a suitable diagram of connections of controlling elements and equipment. The controlled parameter is the final roughness of a cut wall; in the design, the roughness is program-regulated according to the continuously measured root mean square of sound pressure level by means of continuous control of the traverse speed of cutting head.

The paper deals with the automation of the hydroabrasive production process, which leads to higher productivity and production optimization. In the submitted work, the basis of control design is a topography function of surface roughness of abrasive waterjet cut walls, and its functional relations to the controlled speed and to the measured mean values of sound pressure level, including a design of a suitable diagram of connections of controlling elements and equipment. The controlled parameter is the final roughness of a cut wall; in the design, the roughness is program-regulated according to the continuously measured root mean square of sound pressure level by means of continuous control of the traverse speed of cutting head.
Proposal for a method of measurement and control of surface quality in the course of abrasive waterjet cutting of material
Keywords: abrasive water jet; stainless steel; high-pressure water flow; abrasive mass flow; abrasive nozzle diameter; cutting head feed rate; material thickness; surface roughness; abrasive water jet; stainless steel; high-pressure water flow; abrasive mass flow; abrasive nozzle diameter; cutting head feed rate; material thickness; surface roughness